2021
DOI: 10.1186/s40360-021-00507-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of melittin on isoniazid- and rifampicin-induced liver injuries in male albino rats

Abstract: Background The present study investigated the ameliorative effect of melittin, a major polypeptide in the venom of honeybee (Apis mellifera), on isoniazid-(INH) and rifampicin-(RIF) induced hepatotoxicity in male albino rats. Method Thirty rats (140-200 g) were divided into five groups (n = 6): normal control (NC) received normal saline orally (NaCl, 0.9%; toxic (T) group received INH + RIF (each rat received 100 mg/kg, p.o.); melittin (Mel15, Mel3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In this study serum bilirubin levels in drug only induced mice showed a significant (P < 0.01) increase as compared with a normal control group of mice. This study result is in agreement with the data of other authors showing that RIF produced competition for the elimination of bilirubin by the liver [ 49 ] and a combination of INH and RIF resulted in a higher rate of inhibition hepatic clearance of bile, an increase in lipid peroxidation in the hepatocyte, and cytochrome P450 involved in the synergistic effect of RIF and INH [ 30 , 50 , 51 ]. Whereas O. integrifolia leaves extract induced mice challenged with INH and RIF (G IV) did not show a significant difference as compared with the normal control group.…”
Section: Discussionsupporting
confidence: 93%
“…In this study serum bilirubin levels in drug only induced mice showed a significant (P < 0.01) increase as compared with a normal control group of mice. This study result is in agreement with the data of other authors showing that RIF produced competition for the elimination of bilirubin by the liver [ 49 ] and a combination of INH and RIF resulted in a higher rate of inhibition hepatic clearance of bile, an increase in lipid peroxidation in the hepatocyte, and cytochrome P450 involved in the synergistic effect of RIF and INH [ 30 , 50 , 51 ]. Whereas O. integrifolia leaves extract induced mice challenged with INH and RIF (G IV) did not show a significant difference as compared with the normal control group.…”
Section: Discussionsupporting
confidence: 93%
“…The above results suggested that BV is a promising alternative treatment option for non-alcoholic fatty liver disease ( Hanafi et al, 2018 ). BV and honey showed protective effects on hepatoxicity and lipid peroxidation in rats caused by LPS and carbon tetrachloride, while MEL possessed hepatoprotective activity on isoniazid- and rifampicin-induced liver hepatoxicity in rats, both of which suggested that a combination of BV and honey, or MEL could be beneficial for the prevention of hepatoxicity and could be used as potential therapeutic agents ( Meligi et al, 2020 ; Naji et al, 2021 ). Besides, after treatment with bvPLA 2 , the levels of cholestasis markers in the serum were attenuated, the abnormal state of liver fibrosis was restored, and hepatocyte inflammation and apoptosis were inhibited in mice with diet feeding 3,5-diethoxycarbonyl-1,4-dihydrocollidine ( Kim J.-Y.…”
Section: Protect Effect On Liver Kidney Lung and Muscle Injurymentioning
confidence: 99%
“…in wistar rats [9]. Naji et al attained hepatoprotective activity of velittin on isoniazed and rifampicin induced liver injury in male albino rats [61]. Farid et al deliberated anti inflammatory, antioxidant and hepatoprotective effects of Lactoferrin in rats [25].…”
Section: Hepatoprotection Against Chemicalsmentioning
confidence: 99%